ANALISIS SIMULASI KEKUATAN DAN PEMBUATAN RANGKA KENDARAAN SEPEDA MOTOR LISTRIK - Ricky Setiawan; Didik Sugiyanto; Asyari Dariyus (Universitas Negeri Jakarta, 2023)
The development of the automotive industry, especially my vehicle transportation, has changed from a fuel motor to an electric motor vehicle. The purpose of writing is to get results from the simulation of frame design and power on an electric motorcycle. The simulation result from the design where the material used is low carbon steel that the frame of an electric motorcycle with a rider weight of 170 kg is safe based on the